Whole exome sequencing of cell-free DNA – A systematic review and Bayesian individual patient data meta-analysis. (February 2020) - Bos, Manouk K.; Angus, Lindsay; Nasserinejad, Kazem; Jager, Agnes; Jansen, Maurice P.H.M.; Martens, John W.M.; Sleijfer, Stefan
Highlights: WES is an attractive tool for identification of genomic signatures and discovery of resistance mechanisms. Individual patient data meta-analysis showed that the sensitivity of WES of cfDNA is 50% using tumor tissue as reference. The overall agreement between cfDNA and matched tumor tissue is 31% A sub-analysis of samples with a ctDNA fraction ≥ 25% improved sensitivity to 69% and agreement to 46% Currently, there is a large variability in pre- and post-analytical conditions of WES of cfDNA. To this end, standardization of methodologies is highly needed to further define the clinical utility of this promising approach. Abstract: Molecular profiling of tumor derived cell free DNA (cfDNA) is gaining ground as a prognostic and predictive biomarker. However to what extent cfDNA reflects the full metastatic landscape as currently determined by tumor tissue analysis remains controversial. Though technically challenging, whole exome sequencing (WES) of cfDNA enables thorough evaluation of somatic alterations. Here, we review the feasibility of WES of cfDNA and determine the sensitivity of WES-detected single nucleotide variants (SNVs) in cfDNA on individual patient data level using paired tumor tissue as reference ( shared SNVs All tissue SNVs × 100 % ). The pooled sensitivity was 50% (95% credible interval (CI): 29–72%). The tissue mutant allele frequency (MAF) of variants exclusively identified in tissue was significantly lower (12.5%, range: 0.5–18%) than the tissue MAF of variants identified in both tissue and cfDNA (23.9%, range: 17–38%), p = 0.004. The overall agreement ( shared SNVs All SNVs × 100 % ) between SNVs in cfDNA and tumor tissue was 31% (95% CI: 15–49%). The number of detected SNVs was positively correlated with circulating tumor DNA (ctDNA) fraction (p = 0.016). A sub analysis of samples with ctDNA fractions ≥ 25% improved the sensitivity to 69% (95% CI: 46–89%) and agreement to 46% (95% CI: 36–59%), suggesting that WES is mainly feasible for patients with high ctDNA fractions. Pre- and post-analytical procedures were highly variable between studies rendering comparisons problematic. In conclusion, various aspects of WES of cfDNA are largely in its investigative phase, standardization of methodologies is highly needed to bring this promising technique to its clinical potential.